2018
DOI: 10.1002/elps.201800152
|View full text |Cite
|
Sign up to set email alerts
|

Massively parallel sequencing of 12 autosomal STRs in Cannabis sativa

Abstract: Massively parallel sequencing (MPS) is an emerging technology in the field of forensic genetics that provides distinct advantages compared to capillary electrophoresis. This study offers a proof of concept that MPS technologies can be applied to genotype autosomal STRs in Cannabis sativa. A custom panel for MPS was designed to interrogate 12 cannabis-specific STR loci by sequence rather than size. A simple workflow was implemented to integrate the custom PCR multiplex into a workflow compatible with the Ion Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Currently, the two most comprehensive commercial CE-kits for Y-STR DNA profiling are the PowerPlex Y23 (23 Y-STRs, Promega) and the Yfiler Plus PCR Amplification Kit (27 Y-STRs, Applied Biosystems) [ 33 ]. With MPS, a large number of markers (both Y-SNPs and Y-STRs) can be analyzed simultaneously, reaching a higher discrimination capacity and wider range of applications [ 32 , 34 ]. To date, several MPS panels are already commercialized for SNP identity and ancestry analysis as well as STR marker DNA profiling.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the two most comprehensive commercial CE-kits for Y-STR DNA profiling are the PowerPlex Y23 (23 Y-STRs, Promega) and the Yfiler Plus PCR Amplification Kit (27 Y-STRs, Applied Biosystems) [ 33 ]. With MPS, a large number of markers (both Y-SNPs and Y-STRs) can be analyzed simultaneously, reaching a higher discrimination capacity and wider range of applications [ 32 , 34 ]. To date, several MPS panels are already commercialized for SNP identity and ancestry analysis as well as STR marker DNA profiling.…”
Section: Introductionmentioning
confidence: 99%
“…Houston et al reported an MPS panel for the Ion S5™ consisting of twelve autosomal STRs in Cannabis sativa (marijuana). Results showed concordance with CE methods, and isoalleles were found at eight of the loci, providing a higher discriminatory power compared to CE (Houston et al, 2018a , b ). MPS has been also been used for DNA barcoding studies in animals and has shown better recovery, reduced costs, and faster processing times compared to traditional Sanger sequencing (Shokralla et al 2015 ).…”
Section: Introductionmentioning
confidence: 86%
“…Chilean samples were provided by collaborators in the form of DNA extracts. Chloroplast DNA was quantified using a real-time PCR method reported by Houston et al (Houston et al, 2018a , b ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the observations of the sequence variations which derived high polymorphisms of some autosomal STR loci in Hainan Li population and other populations that the variations also existed [84,[111][112][113][114][115][116][117][118][119][120][121][122][123][124], it indicated that the sequence variation-derived high polymorphisms widely existed in different populations, and the genetic diversity of the same locus in different populations were diverse under some circumstances. It could be explained by the relatively isolations between populations from the cultural, geographical and social differences, and genetic mutations accumulated over many years in populations.…”
Section: Str Sequence Variations Observed By the Sequence-based Methodsmentioning
confidence: 99%